Bcl2 inhibits recruitment of Mre11 complex to DNA double-strand breaks in response to high-linear energy transfer radiation - Xie, Maohua (Nucleic Acids Res, 2015)
High-linear energy transfer ionizing radiation, derived from high charge (Z) and energy (E) (HZE) particles, induces clustered/complex DNA double-strand breaks (DSBs) that include small DNA fragments, which are not repaired by the non-homologous end-joining (NHEJ) pathway. The homologous recombination (HR) DNA repair pathway plays a major role in repairing DSBs induced by HZE particles. The Mre11 complex (Mre11/Rad50/NBS1)-mediated resection of DSB ends is a required step in preparing for DSB repair via the HR DNA repair pathway. Here we found that expression of Bcl2 results in decreased HR activity and retards the repair of DSBs induced by HZE particles (i.e. (56)iron and (28)silicon) by inhibiting Mre11 complex activity. Exposure of cells to (56)iron or (28)silicon promotes Bcl2 to interact with Mre11 via the BH1 and BH4 domains. Purified Bcl2 protein directly suppresses Mre11 complex-mediated DNA resection in vitro. Expression of Bcl2 reduces the ability of Mre11 to bind DNA following exposure of cells to HZE particles. Our findings suggest that, after cellular exposure to HZE particles, Bcl2 may inhibit Mre11 complex-mediated DNA resection leading to suppression of the HR-mediated DSB repair in surviving cells, which may potentially contribute to tumor development.